Decline in Estrogen Levels and Its Impact on Muscle Strength in Elderly Women: A Systematic Review - Cahyaningrum, Hapsari; Silanurrahmi, Athaya Zuhra; Hakim , Gamadhan Kholid Rahman (Indonesian Journal of Medicine, 2024)
Background: In the musculoskeletal system, old age is closely related to a decline in muscle strength. Decreased muscle strength in women is caused by the influence of changes in estrogen hormone levels. Several studies were conducted to see how estrogen affects muscle mass, muscle function, muscle damage, muscle regeneration, inflammation in the body, mitochondrial funct¬ion, and substrate metabolism. Therefore, the study was carried out with the aim of conducting further study focusing on estrogen on muscle strength in elderly women.Subjects and Method: The study was conducted with a systematic review design. The study was carried out in accordance using PRISM guidelines with the PICO formula. Population: elderly women, Intervention: estrogen hormone, Outcome: muscle weakness. Article searches were carried out through several databases, namely PubMed, Cochrane Library, Scopus Database, and Physio-therapy Evidence Database (PEDro) with the keywords: estrogen OR "estrogen hormone" OR "muscle strength" OR "risk of falls" OR "menopause" OR "women elderly." Risk of bias assessment was carried out according to the study design of each article.Results: There were 10 articles involved in this study. The article has a cross-sectional and longitudinal study design. Articles had a low and medium risk of bias assessment. 6 articles stated that there was a relationship between changes in estrogen hormone levels and muscle weakness. 4 articles stated that there was no relationship between changes in estrogen hormone levels and muscle weakness. Conclusion: There is a inconsistent relationship between estrogen levels and muscle strength in elderly women.